Business communication : concepts, cases and applications - Chaturvedi, P. D. (Always learning., 2011)
The second edition of Business Communication: Concepts, Cases, and Applications builds on the key strengths of the first edition, clear writing style and comprehensive content, by updating the material to reflect the latest research and technological developments in business communication and presenting it in a style that engages the reader.